Strategi Wakil Kepala Sekolah Bidang Kesiswaan Dalam Penerapan Kedisiplinan Siswa SMP Plus Al-Ma’arif Buntet - khodijah dijah; M.Irhamunna’iem; Sofandi (IAIC (Institut Agama Islam Cirebon), 2020)
Discipline is an action in obeying every rule that has been set, as well as student discipline in obeying the rules at school. Discipline makes students more orderly and organized in carrying out their lives and students also understand that discipline is very, very important for their future, because it can build a strong student personality and can be expected to be useful for all parties. This study aims to determine how the vice principal's strategy for student affairs in instilling student discipline values. The type of research used is qualitative research using observation and interview data collection techniques. In this study, the informants taken were the Principal, Deputy Principal for Student Affairs and one homeroom teacher. The findings of this study show that the strategy of the vice principal in the field of student affairs in instilling the values of discipline in the students of SMP Plus AL-Ma'arif is maximal enough then the supporting factors for the vice principal of the student body work together in disciplining the existing students. The inhibiting factor is that there are still some students who often come late to school and don't wear uniforms according to the schedule or days determined by the school. The solution to the inhibiting factor is that the vice principal for student affairs is more assertive in giving warnings, sanctions or punishments in accordance with existing regulations so that in doing so makes students more disciplined.